Strategi Promosi, Diskon Dalam Peningkatan Penjualan Dengan Google Review - Farel Habiburahman; Najwa Meidinar Eka Raysha; Tasya Fahmi Maharani; Helin Garlinia Yudawisastra (Indonesia Economic Journal, 2026)
Promotional strategies and discounts to increase sales through Google Reviews are crucial in modern marketing because they can influence consumer perceptions and purchasing decisions. This study aims to analyze the influence of promotional strategies and discounts on sales growth in the context of modern marketing. The method used was a literature review by reviewing journal articles, books, and relevant scientific sources. The results of the study indicate that promotions, particularly in the form of price discounts, can increase sales volume because consumers perceive a higher economic value compared to the normal price. The presence of Google Reviews also strengthens the effectiveness of promotions through consumer reviews, which play a role in building trust and purchasing interest. Promotions that are designed appropriately, consistently, and in accordance with market characteristics have proven effective in encouraging purchases and helping companies achieve sales targets. However, promotional effectiveness is highly dependent on the accuracy of budget allocation, consumer targets, and implementation intensity. Excessive promotions have the potential to reduce the perception of product value and shape consumer behavior that only makes purchases during promotional programs. Overall, the study findings confirm that promotional strategies and discounts supported by Google Reviews are strategic marketing instruments capable of increasing sales when managed in a planned and measurable manner for the sustainability of company performance.